Productivity Measurement: Alternative Approaches and Estimates - Peter Mawson; Kenneth I Carlaw; Nathan McLellan (New Zealand Government, The Treasury, 2003)
This paper provides a review of conceptual and methodological issues in measuring productivity. Attention is given to the concept of productivity and the relationship between productivity and technological change. Different approaches to measuring productivity are surveyed and the results from a number of NZ productivity studies are summarised. The availability of appropriate input and output data is essential for the accurate measurement of productivity and therefore this paper also discusses some important data issues that influence productivity measurement.
Keywords: O30; O47; 330; Productivity; Measurement Issues; New Zealand; Technological Change